Yeast Sec14‐like lipid transfer proteins Pdr16 and Pdr17 bind and transfer the ergosterol precursor lanosterol in addition to phosphatidylinositol. Issue 4 (21st December 2022) - Šťastný, Dominik; Petrisková, Lívia; Tahotná, Dana; Bauer, Jacob; Pokorná, Lucia; Holič, Roman; Valachovič, Martin; Pevala, Vladimír; Cockcroft, Shamshad; Griač, Peter
Abstract : Yeast Sec14‐like phosphatidylinositol transfer proteins (PITPs) contain a hydrophobic cavity capable of accepting a single molecule of phosphatidylinositol (PI) or another molecule in a mutually exclusive manner. We report here that two yeast Sec14 family PITPs, Pdr16p (Sfh3p) and Pdr17p (Sfh4p), possess high‐affinity binding and transfer towards lanosterol. To our knowledge, this is the first identification of lanosterol transfer proteins. In addition, a pdr16Δpdr17Δ double mutant had a significantly increased level of cellular lanosterol compared with the corresponding wild‐type. Based on the lipid profiles of wild‐type and pdr16Δpdr17Δ cells grown in aerobic and anaerobic conditions, we suggest that PI‐lanosterol transfer proteins are important predominantly for the optimal functioning of the post‐lanosterol part of sterol biosynthesis. Abstract : Yeast Sec14 family phosphatidylinositol (PI) transfer proteins Pdr16p (Sfh3p) and Pdr17p (Sfh4p) possess high‐affinity binding and transfer towards lanosterol. In addition, a pdr16Δpdr17Δ double mutant had a significantly increased level of cellular lanosterol. Based on the lipid profiles of pdr16Δpdr17Δ cells grown in aerobic and anaerobic conditions, we suggest that PI‐lanosterol transfer proteins are important predominantly for the optimal functioning of the post‐lanosterol part of sterol biosynthesis.